(untitled) (Aporte Santiaguino, 2025)
Pear melon is native to the Andes and is commonly propagated through vegetative structures such as cuttings, which allow for the preservation of the mother plant’s characteristics. Therefore, the objective of this research is to evaluate the effect of worm compost leachate and powdered IBA on the multiplication of Solanum muricatum from cuttings in sand and agricultural soil. Melon pear cuttings were obtained and, according to the treatments, powdered IBA and 1.0% and 1.5% worm compost leachate were applied by immersing the basal part for 2 hours in the leachate. They were then planted in sand and agricultural soil beds. The results indicate that, in the sand, the incorporation of powdered IBA or 1.5% worm compost leachate promoted rooting, with values of 88.89% in treatments 2 and 4, followed by treatments 1 and 3 with 77.8% and 66.67%, respectively. Likewise, the use of IBA in agricultural soil promotes plant rooting.